Potlatch as pedagogy : learning through ceremony - Davidson, Sara Florence, 1973-; Davidson, Robert, 1946- (Portage & Main Press, 2018)
Banned for 67 years by the Canadian government, the potlatch, the foundational ceremony of the Haida people, determined social structure, transmitted cultural knowledge, and redistributed wealth. When these public ceremonies were revived in 1969 by the Elders who collectively remembered the historical ways, the potlatch was embraced by a new generation, who reclaimed practices that had almost been lost forever. Sara Florence Davidson, an educator, saw how these traditions, learned from her father, renowned artist Robert Davidson, could be integrated into contemporary educational practices. In.